Mycetoma revisited - Hassan Iffat; Keen Abid (Our Dermatology Online, 2011)
Mycetoma or 'Madura foot' is a chronic infection of skin and subcutaneous tissues, fascia and bone. It may be caused by true fungi (eumycetoma) or by filamentous bacteria (actinomycetoma). The lesions are composed of suppurating abscesses and draining sinuses with the presence of grains which are characteristic of the etiologic agents. The introduction of new broad spectrum antimicrobials and antifungals offers the hope of improved drug efficacy. This article discusses the historical aspects, epidemiology, clinical findings, laboratory diagnosis and treatment of mycetoma.